The Role of Songket Silungkang Training Instructorsin Equipping Housewife's Work Skills (Case Study) In Songket Lunto Dolas - Ningsih, Widiya Hulan; 'Aini, Wirdatul (Universitas Negeri Padang, 2023)
This research is based on the success of a Songket Silungkang training in equipping the work skills of housewives who do not yet have permanent jobs in Lunto Village. The success of the training is due to the important role of instructors during the training so that all Songket Silungkang training participants are able to work and produce appropriate products. with what is taught by the instructor. This research aims to determine the role of instructors as follows: (1) In providing training participants with skills (2) In developing the attitude and mentality of the training participants (3) In developing the work discipline of the training participants (4) In providing new knowledge to the songket silungkang training participants. This research is a case study with a qualitative approach. The research setting was carried out in East Lunto Village, Lembah Segar District, Sawahlunto City. The data sources for the research were obtained from the research subjects and research informants, with the research subjects namely the Silungkang Songket Instructor and Owner of the Dolas Songket Production House and the Research Informants namely the Silungkang Songket training participants. Data collection techniques include interviews, observation and documentation. The validity of the data obtained from this research is by source triangulation. The results of the research show that there are: (1) The role of the Silungkang Songket Instructor in providing the skills of the training participants is very good (2) The role of the Silungkang Songket Instructor in cultivating attitudes and mentality to provide positive results from before the training (3) The role of the Silungkang Songket Instructor in fostering work discipline so that motivating time discipline for training participants (4) The role of Songket Silungkang Instructors in providing new knowledge to training participants so that they can be implemented at work.Keywords : Role, Instructor, Training, Employability